A Dynamic Hashing Algorithm Suitable for Embedded System - Li Jianwei; Chen Huijie (Institute of Advanced Engineering and Science, 2013)
With the increasing of the data numbers, the linear hashing will be a lot of overflow blocks result from Data skew and the index size of extendible hash will surge so as to waste too much memory. This lead to the above two Typical Dynamic hashing algorithm don’t suitable for embedded system that need certain real-time requirements and memory resources are very scarce. To solve this problem, this paper was proposed a dynamic hashing algorithm suitable for embedded system combining with the characteristic of extendible hashing and linear hashing.it is no overflow buckets and the index size is proportional to the adjustment number. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2672